KOMUNIKASI ORGANISASI DALAM MENGELOLA INFORMASI PUBLIK MELALUI MEDIA SOSIAL DI KEPOLISIAN DAERAH SUMATERA BARAT - Trisusilo, Niko; Chatra, Emeraldy; Arif , Ernita (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
This research explores organizational communication in managing public information through social media in the West Sumatra Regional Police using a qualitative approach, especially case studies. By applying the constructivism paradigm, this research aims to provide a comprehensive picture of organizational communication practices in law enforcement agencies. Primary data was obtained through interviews and direct observation, while secondary data was obtained from documentation and relevant literature. The data analysis technique uses an interactive model, which involves four steps: data collection, data reduction, data presentation, and drawing conclusions. The results of this research show the importance of effective management of public information through social media to maintain public trust and improve the image of law enforcement institutions. The findings and recommendations from this research can serve as a basis for improving and developing organizational communication practices in law enforcement agencies and similar institutions. The implications of this research also stimulate thought to further investigate more effective communication strategies in rapidly evolving contexts such as social media. Thus, this research not only provides valuable insights into organizational communication practices, but also makes an important contribution in the context of public information management in today's digital era.